GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG BOUNDING ATTACHMENT DI BPS SUPATMI BULU TAHUN 2025 - Handayani, Dwi Sri (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Bounding attachment is a bond that develops between parents and a newborn baby, which involves the expression of affection and mutual emotional interaction. Bounding attachment is one of the important factors in the success of exclusive breastfeeding. Breast milk not only provides optimal nutrition but also warmth and emotional comfort, thereby maintaining emotional bonding and emotional attachment between mother and child. The level of family knowledge, especially maternal knowledge, plays a significant role in the success of bounding attachment. The objective of this study was to describe the level of knowledge of pregnant women regarding bounding attachment. The benefit of this study was to obtain data describing pregnant women’s level of knowledge about bounding attachment. This study employed a descriptive observational design with a cross-sectional approach. A total of 30 pregnant women participated in this study, selected using accidental sampling. The study was conducted from Agustus 2025. Data were collected using a questionnaire that had been tested for validity and reliability. The results showed that out of 30 respondents, 5 respondents (16.67%) had good knowledge of bounding attachment, 20 respondents (66.67%) had moderate knowledge, and 5 respondents (16.67%) had poor knowledge. In conclusion, most pregnant women at BPM Supartmi Bulu Sukoharjo had a moderate level of knowledge regarding bounding attachment, accounting for 20 respondents (66.67%).